Evolución y simbiosis de las propensiones esenciales en el escenario de la enseñanza de las ciencias experimentales - Sauleda Parés, N.; Martínez Ruiz, M. A. (Enseñanza de las Ciencias. Revista de investigación y experiencias didácticas, 1994)
The main prospects on science teaching are analyzed. The recent paradig us in computer technology have enabled the development of a second generation of instructional design. Additionally, breakthroughs in neuroscience provide a new focus to ecology in the field of science teaching in the general scenario defined by the theory of evolution. The authors have the conviction that the time has arrived for a new curriculum in sciences based on a symbiosis between computer technology, instructional design and neurobiology. As a consequence, curricular projects in sciences must be especially centered upon neuronal education. Finally, the incidence of the science of complexity and the concept edge of chaos in education is considered.